2020
DOI: 10.1111/ijac.13588
|View full text |Cite
|
Sign up to set email alerts
|

Key features in the development of unimorph stainless steel cantilever with screen‐printed PZT dedicated to energy harvesting applications

Abstract: The design and processing of vibrational energy harvester based on screen-printed piezoelectric lead zirconate titanate (Pb(ZrxTi1-x)O3 (PZT)) are described here. Two different structures, a simple cantilever and a complex zigzag geometry made of PZT layer sandwiched between gold electrodes and supported on a metallic stainless steel substrate have been successfully fabricated by screen printing thick film technique. Compared to bulk PZT ceramics, the main limiting features at different scales are porosity, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The addition of only 3% in weight of LBCu was shown to be efficient for PZT sintering, both the melting of the binary system Bi2O3-Li2CO3 and the presence of CuO play a significant role in lowering the sintering temperature [47,48]. For bounded layers, a diffusion/adhesion layer is formed between the substrate and the Au layer, as already observed in [40,42]. In the case of the free-standing PZT layer, only a slight diffusion of Sr into the Au layer is observed, showing the efficiency of the Au electrode as a barrier to limit PZT/SrCO3 crossdiffusion (Figure 5c).…”
Section: Mineral Approachmentioning
confidence: 65%
See 3 more Smart Citations
“…The addition of only 3% in weight of LBCu was shown to be efficient for PZT sintering, both the melting of the binary system Bi2O3-Li2CO3 and the presence of CuO play a significant role in lowering the sintering temperature [47,48]. For bounded layers, a diffusion/adhesion layer is formed between the substrate and the Au layer, as already observed in [40,42]. In the case of the free-standing PZT layer, only a slight diffusion of Sr into the Au layer is observed, showing the efficiency of the Au electrode as a barrier to limit PZT/SrCO3 crossdiffusion (Figure 5c).…”
Section: Mineral Approachmentioning
confidence: 65%
“…In this section, since some studies have already reported PZT screen-printing on silicon [37,38] followed by its release, only thick films printed on ceramic substrates and partially or completely dissociated from the substrate are considered. Bounded screen-printed PZT layers can be found in the literature [39][40][41][42], and more recently lead-free piezoelectric layers [43]; however, to the best of our knowledge, only screen-printed PZT thick films have been released from the substrate. When processing screen-printed PZT thick films using a conventional process, the PZT layers contain a residual porosity.…”
Section: Pzt Thick-film Ceramic Memsmentioning
confidence: 99%
See 2 more Smart Citations
“…In most cases, the structure of an energy scavenger is a cantilever beam with a piezoelectric layer [16,17]. Because of their relatively low resonance frequency and relatively high strain average per specific loading, cantilever beams are considered important [18].…”
Section: Introductionmentioning
confidence: 99%